Exploring the relationship between competition and innovation in Norwegian SMEs - Øystein Moen; Tord Tvedten; Andreas Wold (Cogent Business & Management, 2018)
This paper explores the relationship between innovation and competition in 380 Norwegian SMEs. In contrast to a large portion of the empiric literature, we utilized the managers' perception of their firm's innovation activities and competitive environment as measures. In particular, this paper aimed to shed some light on this widely debated topic by examining several aspects of innovation and competition, along with including the effects of demand conditions. The results indicate that competition in the form of rapid changes in production technology has the largest overall impact on innovation, and is positively correlated with most innovation indicators. An inverse-U shaped relationship between completion and innovation is only detectable in one out of 60 possible settings. The combination of low levels of competition and high market demand is identified in one group of firms; these are also characterized by a high focus on the development of new products.
Keywords: 650